From Crisis to Recovery: Navigating Sustainable Strategies by Hospitality Providers - Martin Tshepho Chokoe; Lihle Nkomo; Erica A. Sao Joao (African Journal of Hospitality, Tourism and Leisure, 2023)
The COVID-19 pandemic had a far-reaching impact on hospitality businesses and the world has continued along a path with multiple uncertainties, which reinforces the necessity to reevaluate crisis management strategies. Due to shifting hospitality operations and noticeable changes within the business model, there is a need to become more resilient to remain sustainable. This study aimed to determine how COVID-19 affected hospitality providers and to identify strategies operators have used, evaluating their effect going forward, which could be used to improve crisis management. A qualitative study was conducted, with a purposive sampling of hospitality managers or owners within an area of Johannesburg. A total of 15 participants were interviewed using a semi-structured interview design. The collected data was examined using thematic analysis. The research revealed that hospitality managers in a cost-cutting exercise, reduced their costs by retrenching workers, closing businesses, adapting business models, and applying lockdown measures of social isolation and sanitisation. Owners pleaded with the government for financial support to maintain their operations. The management implications of this research encourage a greater awareness of preparation for future pending crises and will be useful to hospitality business owners as they create contingency plans and resilience strategies.